La simulación de negocios herramienta de aprendizaje y desarrollo empresarial: http://repositorio.ulvr.edu.ec/handle/44000/3628 - González Márquez, José Luis (2019)
The purpose of this paper is to explain the heterogeneity in the adoption of information technologies from the access of the company to information channels. Business simulation is currently a business learning strategy, in response to training needs in the business sector. The objective of this article is to determine the impact that the use of business simulators has on business projects, demonstrating the impact of information simulation with economic growth. In summary, the research analyzes bibliographical sources on the widespread application of information and communication technologies (ICT), in studies that try to understand, analyze, and explain their impact on the market through simulation. The applied methodology contains a descriptive, observational, and transversal character of relational type, where the theory and the use of the practice of the business simulator are combined; as an optimal tool for learning that allows you to manage a virtual company. The conclusions obtained identify that there is a relationship between business simulation as a business learning strategy and training in the business sector, most of them find a direct and positive link between the use of ICT and productivity, allowing the development of the simulation of data, which has evolved over time and according to technological progress.